Avaliação da necessidade do uso de rotina da recuperação intraoperatória de sangue no transplante hepático - Lima, Claudianne Maia De Farias (2020)
Liver cirrhosis is considered the final stage of a variety of liver disease processes of various causes, and liver transplantation is approved as the most appropriate treatment for patients with end-stage liver disease. Since it is a highly complex procedure involving several vascular anastomoses, there is a significant risk of perioperative bleeding. Haemotherapy has been qualified to minimize transfusion risks. Routine use of cell salvage during surgery reduces the use of allogeneic blood. The aim of this study was to evaluate the need for routine use of intraoperative blood salvage (IOS) in liver transplantation. 327 liver transplants, performed from 2014 to 2016, were included in the research. The collected data included pre-transplant exams, the red blood cell transfusions during the transplant and data from the cell salvage. Statistical analyzes were performed using the statistical program JAMOVI and Microsoft Excel 2016. The median age was 54 years, 66% (219) were males and the most prevalent blood type was group O, counting for 48% (155). The most frequent etiologies for cirrhosis were hepatitis C, with 33.8% (114), and alcohol, with 98 (30,1%). Among the 327 transplants, there was a red blood cell transfusion in 110 (34%), with a median of 2. In 173 transplants with cell salvage, there was a median recovered volume of 417 ml and a red blood cell transfusion in 78 (45.1%) transplants, with a median of 0. In this group, the median MELD was 22 and the cold ischemia time was 300 minutes. Without the use of cell salvage, 92 transplants were performed and they were transfused in 19, with a median of 0. In this group, the MELD (Model End-Stage Liver Disease) median was 20 and the cold ischemia time was 281 minutes. The MELD score and the time of cold ischemia were pointed out as significant variables for bleeding. The cost of IOS service equals 2.6 CH. In the group that recovered the most blood, the volume is approximately 2 CH. There was no relationship between IOS use, transfusion and tumor characteristics with hepatocellular carcinoma recurrence in patients. We concluded in the present study that there is no need to use the cell retriever in all liver transplants, the greatest indication being patients with portal vein thrombosis and changes in creatinine values.